MANAJEMEN ASET KENDARAAN DINAS PEMERINTAH KABUPATEN KUANTAN SINGINGI - Suryaningsih, Dewi; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Problems in asset management often arise in local governments, especially official vehicle assets in the Kuantan Singingi Regency government. Problems that occur are often caused by the recording of assets that have not gone well. This study aims to explain in detail the asset management of Kuantan Singingi Regency government vehicles, and to describe the factors that influence the management of Kuantan Singingi Regency government vehicle service assets. This research is a descriptive study with qualitative research methods. Data collection techniques are done by analyzing data in qualitative research. The results showed that the management of official vehicle assets in Kuantan Singingi Regency was still not as expected, this is because the recording of official vehicle data in Kuantan Singingi Regency had not been carried out as a whole, this was influenced by manual recording, lack of human resources, and then data old vehicles that have not been inventoried Keywords: Management, Assets, Asset Management, Official Vehicles.